Frankreich im KSZE-Prozess : Diplomatie im Namen der europäischen Sicherheit 1969-1983 - Heyde, Veronika 1977- (Quellen und Darstellungen zur Zeitgeschichte, 2017)
"The CSCE process was largely responsible for keeping alive East-West dialogue during the crisis-ridden period of the 1970s and 80s. France, in full solidarity with the interests of West Germany and with its own important motivations, helped to shape this process through its own disarmament initiative, which continued to have an impact well into the future